Osseodensification -- A systematic review and qualitative analysis of published literature - Ninad Milind Padhye; Ashvini Mukul Padhye; Neel B. Bhatavadekar (Elsevier, 2020)
The recently introduced technique of osseodensification for dental implant involves the use of special drills (Densah) run in a counter-clockwise direction at the osteotomy site. It is claimed that this causes expansion of the osteotomy site, and increases density of the bone in immediate vicinity of the osteotomy. We reviewed published papers on the primary stability attained using this drilling technique. As a secondary finding, the bone to implant contact (BIC) and the bone area fraction occupancy (BAF) was also compared between the conventional drilling protocol and the osseodensification protocol, among these articles. A Systematic search was performed in PubMed-Medline, Embase and Google Scholar for clinical/animal studies up to November 2018. A total of 12 articles, from a database of 132 articles, consisting of 8 animal histologic studies, 2 human based clinical studies, 1 case series and 1 case report were assessed. 10/12 articles measured the insertion torque values, 7/12 articles measured the BIC and 6/12 articles estimated the BAF between the two techniques. Quality assessment of 8 studies performed using ARRIVE guidelines showed that 6/8 studies had a high score. An average increase in the insertion torque, BIC and BAF was noted in the osseodensification group as compared to the conventional drilling group. Since most of these studies are non-clinical, it can be inferred that osseodensification is an efficient way to enhance primary stability of implants in low density bone in an animal model. However, extrapolation to long term clinical success cannot be ascertained until further evidence becomes available.